Pemecahan Asymmetric Capacitated Vehicle Routing Problem with Time Windows (ACVRPTW) dengan Algoritma Ant Colony Optimization (ACO) - David Try Liputra (Universitas Katolik Parahyangan, 2023)
One of the main aspects that determines the successful of managing a supply chain system or supply chain management (SCM) is transportation planning. The problem of determining vehicle routes or commonly known as the vehicle routing problem (VRP) is one of the important studies in transportation planning at the operational level. Determining the right vehicle routes can increase the effectiveness and efficiency of a transportation system and related supply chain systems. This research focuses on the asymmetric capacitated vehicle routing problem with time windows (ACVRPTW), which is a vehicle routing problem that takes into account vehicle capacity, asymmetric return distances between customers, and delivery time constraints. A mathematical model is formulated based on the research objective to be achieved, i.e. minimizing the total shipping costs consisting of travel costs, overtime delivery costs, late delivery compensation costs, and re-delivery costs. Two alternative solution algorithms are developed, namely sequential insertion (SI) and ant colony optimization (ACO). A numerical example is provided to present the results of research on a clothing convection industry, where the ACO algorithm is proven to be able to produce better solutions than the SI algorithm.